Metacomprensión lectora y resolución de problemas de física en alumnos del quinto grado de secundaria del Callao - Damacén Ysla, Leoncio (2012)
The research sought to determine the relationship between metacomprehension and problem solving ability in physics and applied metacomprehension instruments and troubleshooting. These instruments were adapted for this study and applied to a sample of 90 students in the fifth grade of secondary educational institution. It was found that there is a relationship between the two variables of study. Besides the qualitative distribution of the planning dimension for 36.7% of the students in the regular level compared to 16.7% which is in an acceptable level in the dimension of supervision, 46.7% of students regulate the level found in front of a 8.9% which is at a very low level in the assessment dimension, which shows that 44.4% of students located in the regular level versus 5.6% which is in a very low level.